PENDAMPINGAN PEMBUATAN POP-UP BOOK SEBAGAI MEDIA VISUAL PEMBELAJARAN TEMPAT DHARMAYATRA AGAMA BUDDHA UNTUK PEMBINA SEKOLAH MINGGU BUDDHA VIHARA WENING SARI - Supartono, Supartono; Budiadi, Seno; Yoga, Riko Arma; Bagaskara, Sukiman (Yayasan Education and Social Center, 2025)
Sekolah Minggu Buddha (SMB) plays a vital role in imparting Buddhist values to children and youth, yet traditional lecture-based methods often fail to engage students effectively. This community service project aimed to enhance learning at SMB Vimala Sari, Semarang, Indonesia, by developing an interactive Pop-Up Book titled